2019
DOI: 10.1002/jor.24322
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Rich Plasma (PRP) From Older Males With Knee Osteoarthritis Depresses Chondrocyte Metabolism and Upregulates Inflammation

Abstract: There is intense clinical interest in the potential effects of platelet-rich plasma (PRP) for the treatment of osteoarthritis (OA). This study tested the hypotheses that (i) "lower" levels of the inflammatory mediators (IMs), interleukin-1β, and tumor necrosis factor α (TNF-α) and (ii) "higher" levels of the growth factors (GFs), insulin-like growth factor 1, and transforming growth factor β1 within leukocyte-poor PRP correlate with more favorable chondrocyte and macrophage responses in vitro. Samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 31 publications
5
34
0
1
Order By: Relevance
“…These differences may have consequences on the results obtained with treatments based on this technique due to molecular changes in PRP. In fact, diverse studies showed that Aged PRP contains more proinflammatory molecules than Young PRP [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These differences may have consequences on the results obtained with treatments based on this technique due to molecular changes in PRP. In fact, diverse studies showed that Aged PRP contains more proinflammatory molecules than Young PRP [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing evidence regarding PRP and its use in knee OA, the efficacy of PRP remains inconclusive. 8,16,39,43 While it is possible that the various growth factors and catabolic cytokines contained in PRP are involved in its anabolic and anticatabolic effects, 19,36,49 the majority of previous studies did not provide a precise biological characterization of its various components.…”
mentioning
confidence: 99%
“…APS is a blood derivative that provides a milieu of bioactive factors with a high level of anti-inflammatory cytokines while ensuring low levels of proinflammatory molecules 26 ; it also shows in vitro the inhibition of inflammatory cytokines and destructive proteases, with the stimulation of cell proliferation in cartilage tissue. 22,24,26,32 The high concentrations of anti-inflammatory molecules and growth factors can be obtained by all patients regardless of the degree of articular cartilage degeneration and age, thus prompting the use of APS in patients with OA. 25 In a prospective randomized clinical trial, horses with naturally occurring OA demonstrated decreased lameness, which was maintained up to 52 weeks, 3 supporting the rationale to address OA by providing platelets, plasma, and white blood cells.…”
Section: Discussionmentioning
confidence: 99%